2014
DOI: 10.1002/da.22239
|View full text |Cite
|
Sign up to set email alerts
|

Lay Providers Can Deliver Effective Cognitive Behavior Therapy for Older Adults With Generalized Anxiety Disorder: A Randomized Trial

Abstract: Lay providers, working under the supervision of licensed providers, can deliver effective CBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 77 publications
5
82
1
Order By: Relevance
“…It is worth noting that one such study included in this review found no significant difference in effectiveness between CBT provided by expert practitioners (post-doctoral fellows with formal training and experience) and CBT provided 'lay' practitioners (bachelor-level practitioners with no previous mental health training or experience (24)). Further studies investigating the relationship between qualification level and CBT's effectiveness in primary care are particularly needed because many graduate-level practitioners already provide CBT in primary care through initiatives such as IAPT.…”
Section: Clinical Implications and Future Researchmentioning
confidence: 90%
“…It is worth noting that one such study included in this review found no significant difference in effectiveness between CBT provided by expert practitioners (post-doctoral fellows with formal training and experience) and CBT provided 'lay' practitioners (bachelor-level practitioners with no previous mental health training or experience (24)). Further studies investigating the relationship between qualification level and CBT's effectiveness in primary care are particularly needed because many graduate-level practitioners already provide CBT in primary care through initiatives such as IAPT.…”
Section: Clinical Implications and Future Researchmentioning
confidence: 90%
“…34 Effect sizes were based on completers-only data, as intention-to-treat outcome data was not available for all studies. As a number of trials had small samples, effect sizes were corrected using an adjustment, J , to convert effect sizes to Hedges' g. 35 For studies in which multiple treatment arms received CBT, data was collapsed to form one group where treatment was comparable, 36,37 and if not, data from the most relevant CBT group was extracted. 38 In studies in which multiple comparison groups did not receive CBT, data was extracted from the most active comparison condition.…”
Section: Between-group Effect Sizesmentioning
confidence: 99%
“…Two of the remaining 17 studies were excluded, 53,54 due to duplicate data from more appropriate eligible articles. 37,39 A final study was excluded because outcome data had been reported as an anxiety composite. 55 Fourteen…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internet-delivered CBT, on the other hand, can be given to more patients as it requires less therapist involvement, is not time dependent, and is cheaper (115). Therapist guided Internet-delivered CBT is similar to face-to-face treatment with regard to treatment effects (115)(116)(117)(118)(119), despite different therapist backgrounds (120)(121)(122). Guided Internet-delivered CBT has been proven to be effective in the treatment of mild to moderate symptoms of depression and anxiety (104,123), and does not differ from face-to-face treatment.…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%